Valeric Acid Protects Dopaminergic Neurons by Suppressing Oxidative Stress, Neuroinflammation and Modulating Autophagy Pathways - Jayaraj, Richard L. (Int J Mol Sci, 2020)
Parkinson’s disease, the second common neurodegenerative disease is clinically characterized by degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) with upregulation of neuroinflammatory markers and oxidative stress. Autophagy lysosome pathway (ALP) plays a major role in degradation of damaged organelles and proteins for energy balance and intracellular homeostasis. However, dysfunction of ALP results in impairment of α-synuclein clearance which hastens dopaminergic neurons loss. In this study, we wanted to understand the neuroprotective efficacy of Val in rotenone induced PD rat model. Animals received intraperitoneal injections (2.5 mg/kg) of rotenone daily followed by Val (40 mg/kg, i.p) for four weeks. Valeric acid, a straight chain alkyl carboxylic acid found naturally in Valeriana officianilis have been used in the treatment of neurological disorders. However, their neuroprotective efficacy has not yet been studied. In our study, we found that Val prevented rotenone induced upregulation of pro-inflammatory cytokine oxidative stress, and α-synuclein expression with subsequent increase in vital antioxidant enzymes. Moreover, Val mitigated rotenone induced hyperactivation of microglia and astrocytes. These protective mechanisms prevented rotenone induced dopaminergic neuron loss in SNpc and neuronal fibers in the striatum. Additionally, Val treatment prevented rotenone blocked mTOR-mediated p70S6K pathway as well as apoptosis. Moreover, Val prevented rotenone mediated autophagic vacuole accumulation and increased lysosomal degradation. Hence, Val could be further developed as a potential therapeutic candidate for treatment of PD.